Defining Features of The Upper Extremity in Holt-Oram Syndrome - Wall, Lindley B. (J Hand Surg Am, 2015)
PURPOSE: To investigate the distinguishing morphologic characteristics of children with radial longitudinal deficiency (RLD) in Holt-Oram Syndrome (HOS). METHODS: One hundred fourteen involved extremities in 62 patients with a diagnosis of HOS were identified at 3 institutions. Medical records and radiographs were evaluated. RLD and thumb hypoplasia were classified according to the modified Bayne and Klug classification and Blauth classifications respectively, when possible. Other unusual or distinguishing characteristics were catalogued. RESULTS: There was bilateral involvement in 84% of patients. The forearm was involved in 81% of the extremities and a shortened distal radius (Bayne and Klug type I RLD) was the most commonly identified forearm anomaly (40%). Radioulnar synostosis was present in 15% of the extremities, all in the proximal forearms with reduced radial heads. Thumb aplasia (Blauth type V hypoplastic thumb) was the most common type of classifiable thumb abnormality and occurred in 35% of involved thumbs. 27% of abnormal thumbs affected were not classifiable according to the Blauth classification, and 19% of involved thumbs (hypoplastic or absent) had first web syndactyly. CONCLUSIONS: The upper extremity in Holt-Oram Syndrome differs from the typical presentation of radial longitudinal deficiency. The forearm is more often involved and may demonstrate radioulnar synostosis. The thumb is frequently unclassifiable by the Blauth classification and has first web syndactyly. The presence of radioulnar synostosis and syndactyly of the radial 2 digits in RLD should prompt the hand surgeon to obtain a cardiac evaluation and consider genetic testing for HOS. TYPE OF STUDY/LEVEL OF EVIDENCE: Diagnostic III.